2016
DOI: 10.3390/molecules21101357
|View full text |Cite
|
Sign up to set email alerts
|

Small versus Large Iron Oxide Magnetic Nanoparticles: Hyperthermia and Cell Uptake Properties

Abstract: Efficient use of magnetic hyperthermia in clinical cancer treatment requires biocompatible magnetic nanoparticles (MNPs), with improved heating capabilities. Small (~34 nm) and large (~270 nm) Fe 3 O 4 -MNPs were synthesized by means of a polyol method in polyethylene-glycol (PEG) and ethylene-glycol (EG), respectively. They were systematically investigated by means of X-ray diffraction, transmission electron microscopy and vibration sample magnetometry. Hyperthermia measurements showed that Specific Absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
66
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 49 publications
8
66
0
1
Order By: Relevance
“…As can be seen in Figure 6, the application of high frequency 633.1-759 kHz and high amplitude caused a spontaneous rise of the suspension's temperature. The plateau temperature is reached at lower amplitudes, so to reach 45 • C (318 K) the frequencies from 345.5 kHz up to 487.75 kHz and amplitudes 150-200 G are optimal, being within the biophysical limitations for such therapy (the so-called Brezovich limit) [16,24,38].…”
Section: Magnetic Hyperthermiamentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen in Figure 6, the application of high frequency 633.1-759 kHz and high amplitude caused a spontaneous rise of the suspension's temperature. The plateau temperature is reached at lower amplitudes, so to reach 45 • C (318 K) the frequencies from 345.5 kHz up to 487.75 kHz and amplitudes 150-200 G are optimal, being within the biophysical limitations for such therapy (the so-called Brezovich limit) [16,24,38].…”
Section: Magnetic Hyperthermiamentioning
confidence: 99%
“…Heating of nanoparticles up to 41-47 • C (314-320 K) for dozens of minutes by hyperthermia triggers the apoptosis [19,20], destabilizes cell and offsets homeostasis, leading to the higher susceptibility of cancer cells to chemotherapy [21]. Also, hyperthermia can potentiate the effect of radiation and has been shown to improve local treatment in patients with advanced cancers like breast [22] and head and neck [23] metastatic cancers.The values of SAR for iron oxide-based nanoparticles depend on numerous parameters, such as size, shape, structure, composition, surface modifications, suspending medium, tissue localization, as well as AMF amplitude H and its frequency f. In the case of medical application, the product of H and f should be smaller than 5 × 10 9 Am −1 s −1 [24]. However, typical SAR values are within a few hundred watts per gram of nanoparticles [25,26].Our previous studies presented the influence of doping with Ho 3+ on the morphology, magnetic and structural properties of SPIONs for further modification with antitumor drugs, revealing that optimum doping of Ho(III) is between 1 and 2.5% atomic versus total iron content [27].For the application of magnetic hyperthermia, it is very important that the nanoparticles reach tumor cells and stay in place long enough to allow a continued treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 The properties of SPIONs are known to be size dependent, and consequently, the effect that they produce on tissues is varied. 9,10 Another important parameter responsible for toxicity of the SPIONs is the shape of these nanoparticles. It was correspondence: alexander V soldatov; elena a Kuchma The smart Materials research center, southern Federal University of russia, sladkova 178, rostov-on-Don 344090, russia email soldatov@sfedu.ru; elenaku4ma@ yandex.ru shown that rod-shaped nanoparticles were more toxic than the sphere-shaped ones.…”
Section: Introductionmentioning
confidence: 99%
“…Iron nanoparticles (INPs) comprise an important class of nanobiomaterials and have many potential applications in resonance imaging contrast enhancement, tissue repair, drug delivery, cell separation, hyperthermia [1], polymerase chain reaction [2], tissue engineering [3] and deoxyribonucleic acid detection [4]. Moreover, INPs exhibit great potential for applications including data storage [5], water purification [6] and as catalysis [7].…”
Section: Introductionmentioning
confidence: 99%